ANALISIS DAMPAK SERVICE PERFORMANCE (SERVPERF) DAN KEPUASAN TERHADAP LOYALITAS NASABAH STUDI PADA: PT BRISyariah YOGYAKARTA - , Ernisa Fauzia, Dr. Wakhid Slamet Ciptono, MBA., MPM. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research formulation in this study is regarding how service performance affects customer loyalty and whether customer satisfaction moderated the relationship between the two variables. The research population is the customers of PT. Bank BRISyariah KCP A. Dahlan Yogyakarta with a total of 200 questionnaires distributed. Data analysis method in this research uses linear regression analysis. Linear regression results between service performance towards customer loyalty shows that regression coefficient of the variable service performance (X1) is 0.211 with a positive and significant value, it is proven significantly value <0,05. These results mean that service performance affects customer loyalty positively. So, the higher the service performance of employees will affect customer loyalty. Absolute difference value test the result show that coefficient of the variable consumer satisfaction (X1) has a significant and positive result, this result proves that consumer satisfaction is the moderating variable in the relationship between service performance and customer loyalty. Research results show that the positive influence from service performance to customer loyalty will increase if customer satisfaction is also high.